HUBUNGAN KONDISI FISIK LINGKUNGAN RUMAH DENGAN KEJADIAN TUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS PERUMNAS I DAN II KECAMATAN PONTIANAK BARAT - ., Agustian Deny (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: TB cases increased over the last five years in WestKalimantan. Perumnas Clinics I dan II region at West Pontianak Subdistricthave the highest number of cases. It can be influenced by the physicalcondition of the home environment that does not eligible. Purpose: To knowthe association between the physical condition of the home environment withthe incidence of pulmonary TB. Method: A cross sectional analytic study,which used non-probability sampling (consecutive sampling). Total sampleare 60 subjects. Research done by observing the physical condition of thehome environment variables. Data was analyzed by univariate, bivariate (Chisquaretest) and multivariate (logistic regression). Result: The independentvariables that have a significant relationship with the incidence of pulmonaryTB and its risk factor are the density residential, natural ventilation, andnatural lighting either in the dominantly used room and in the bedroom. Whilethe type of flooring and the humidity in the room that predominantly used andthe bedroom did not have a significant relationship with the incidence.Multivariate analysis showed that the probability of a person sufferingpulmonary TB when living in a house with residential density and naturalventilation bedrooms that not eligible are 93%. Conclusion: The physicalconditions of the home environment that have a significant relationship withthe incidence of pulmonary TB are the density residential, natural ventilationand natural lighting either in the predominantly used room and in thebedroom.Keywords: pulmonary TB, risk factors, the physical condition of the home environment1) Medical School, Faculty of Medicine, University of Tanjungpura, Pontianak, West Kalimantan.2) Departement of Pulmonology, dr. Soedarso General Hospital, Pontianak, West Kalimantan.3) Departement of Biochemistry, Faculty of Medicine, University of Tanjungpura Pontianak, West Kalimantan.